1996
DOI: 10.1115/1.2831624
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Phenomena Appearing in EHL Contacts

Abstract: In a previous paper the authors showed that when the surface velocity of a body having lower elastic modulus is faster than that of a body having higher elastic modulus, and when the radius of curvature of the former is larger than that of the latter, a deep conical depression (dimple) is produced in the contact surface. This dimple occurs in place of the flat plateau predicted by the point contact elastohydrodynamic lubrication (EHL) theory. In this paper, the effects of surface kinematic conditions on the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
55
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 7 publications
6
55
1
Order By: Relevance
“…The Kaneta dimple, which cannot be explained by the classical EHL theory, was numerically studied by Yang et al [15][16][17] using the thermal viscosity wedge concept. Their numerical results matched the measurements of Kaneta et al [13,14] well, and they also proved that the dimple could only be formed under pure glass-disc sliding. Hence, Yang et al claimed that the thermal viscosity wedge is the most reasonable explanation for the Kaneta dimple.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…The Kaneta dimple, which cannot be explained by the classical EHL theory, was numerically studied by Yang et al [15][16][17] using the thermal viscosity wedge concept. Their numerical results matched the measurements of Kaneta et al [13,14] well, and they also proved that the dimple could only be formed under pure glass-disc sliding. Hence, Yang et al claimed that the thermal viscosity wedge is the most reasonable explanation for the Kaneta dimple.…”
Section: Introductionsupporting
confidence: 79%
“…In the 1990s, Kaneta et al [13,14] produced highquality images of a dimple-shaped EHL contact in an optical EHL test rig. They reported that a deep central dimple occurred with pure glass-disc sliding, but not with pure ball sliding, even though both cases were the same kinematically (pure sliding).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, they showed abnormal interferograms of their experimental contacts compared with conventional ones, but were not aware that their observed phenomena may be the samc with the earlier findings by Lee et al (1973) for the similar case, which showed anomalous results of film thickness and its vrrricrtion with load in their experiment compared with conventional EHL theories indicating severe film collapse at relatively heavy loads. Surprisingly, Kaneta et al (1996) measured the film thickness higher than conventional EHL theory prediction indicating dimples of their contacts. Their measurement should be rather abnormal, since simple sliding normally results in reduced film thickness compared with conventional EHL theories as measured by Lce et al (1973).…”
Section: Introductioncontrasting
confidence: 59%
“…11 Film thickness profiles obtained for different SRR values and from classical and composite (including nanoscale slip) models zone greatly changes. Even with moderate SRR values (for instance SRR = 0.2), the curvature in the film thickness profile changes sign, as experimentally observed in the literature and referred to as dimple occurrence [33,34]. On the numerical side, Ehret at al.…”
Section: Results and Comparison With The Initial Ehl Solutionmentioning
confidence: 68%